Health motives and health behaviour self-regulation in older adults - Schüz, Benjamin; Wurm, Susanne; Warner, Lisa Marie; Wolff, Julia; Schwarzer, Ralf; Wolff, Julia Katharina (Journal of Behavioral Medicine, 2014)
Health motives are motivational dispositions towards health. They are implicitly inherent in most health behaviour theories, yet rarely studied. We examined the role of health motives in health behaviour self-regulation (physical activity), particularly in the mediation of intention effects on behaviour via planning in an at-risk population with high need for behaviour change, older adults with multiple illnesses. A longitudinal study with two measurement points over 6 months was conducted, assessing 309 community-dwelling adults with multiple illnesses aged 65 and older. Health motives were assessed by contrasting health ratings with all other domains on the Personal Life Investment Schedule. Data were analysed in a moderated mediation framework using path analyses. Health Motives moderated the degree to which intentions predicted behaviour via planning (intention health motives β =.18, p <.05). Intentions are better translated into planning and behaviour if furnished with health motives. For older adults, this suggests that "health" in health behaviour change motivation merits more investigation, for example by stressing functional implications. © 2013 Springer Science+Business Media New York.
Keywords: Health behaviour theories; Health motivation; Health motives; Moderated mediation; Multimorbidity; Older adults; Physical activity